Strategi Pengembangan Wilayah Pesisir di Kecamatan Seririt Kabupaten Buleleng - Rinaldi, Ahmad; Citra, I Putu Ananda; Christiawan, Putu Indra (UNIVERSITAS NEGERI MAKASSAR, 2020)
This research was conducted on the coastal regions in Seririt sub-district. This research aimed to: 1) Describing the potential of coastal resources on Coastal Villages in Seririt sub-district, 2) Analyzing the strategy of developing coastal regions in the Seririt sub-district.Â The method of this research were interview and observation. A purposive sampling technique is used for sampling.Â The data analysis of this research were qualitative descriptive analysis and SWOT analysis. The results showed: 1) Coastal resources on Coastal Villages in Seririt sub-district include: (1) biological resources, there are: the potential of fisheries, coral reefs and turtles, (2) non-biological resources, there are: sand and sea water, (3) artificial resources, there are: canoes, canoe engines and fishing equipments. (4) environmental service resources, there are: marine tourism (canoeing), diving or coral reef's snorkeling, turtle release activity and dolphin attractions. 2) Strategies of developing coastal regions in Seririt District for fish cultivation, preservation of coral reefs and turtles, training for improving tourism services, providing marketing centers for fish, providing training to the communities on conservation of coral reefs, turtles and handicraft production, capital procurement for the communities efforts in producing handicrafts, law enforcement by create awig-awig along with sanctions, providing restrictions for fisheries products from outside the regions, preparing capital or special funding for tourism.